ISOLATION, SELECTION AND MOLECULAR IDENTIFICATION OF ANTIBIOTIC PRODUCING ACTINOMYCETES - Tri Ratna Sulistiyani; Nunuk Widhyastuti (Widyariset, 2011)
Microorganisms is one of the biodiversity that is priceless. One type of microorganisms is actinomycetes. Actinomycetes is a potential source of bioactive compounds producing high comercial value in pharmaceuticals and agricultures. The results showed that 44 Actinomycetes isolates has the ability to produce secondary metabo-lites antibiotics. They were active against M. luteus, S. aureus, E. coli, B. subtilis, S. cerevisiae, and C. albicans. Morphological studied indicated that the A16.1 isolate belonged to the genus Streptomyces. The identifi cation result based on 16S rDNA sequence is S. hygroscopicus subsp. azalomyceticus with 97% similarity level.